2021
DOI: 10.1186/s12891-021-04784-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a ceiling-mounted 3D flat panel detector vs. conventional intraoperative 2D fluoroscopy in plate osteosynthesis of distal radius fractures with volar locking plate systems

Abstract: Objectives To compare intraoperative 3D fluoroscopy with a ceiling-mounted flat panel detector in plate osteosynthesis of distal radius fractures (AO/OTA 2R3C1.2) with volar locking plate systems to conventional 2D fluoroscopy for detection of insufficient fracture reduction, plate misplacement and protruding screws. Methods Using a common volar approach on 12 cadaver forearms, total intraarticular distal radius fractures were induced, manually red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…When the polyaxial VLP is used for the osteosynthesis of distal radius fractures, screw penetration into the joint is one of the most common complications. 14 Nishiwaki et al reported that in the osteosynthesis of unstable intra-articular fractures of the distal radius, screw penetration into the joint occurred in 0 out of 54 cases with the monoaxial VLP and in 4 out of 55 cases with the polyaxial VLP. Therefore, osteosynthesis using the polyaxial VLP was considered to be more prone to technical errors.…”
Section: Discussionmentioning
confidence: 99%
“…When the polyaxial VLP is used for the osteosynthesis of distal radius fractures, screw penetration into the joint is one of the most common complications. 14 Nishiwaki et al reported that in the osteosynthesis of unstable intra-articular fractures of the distal radius, screw penetration into the joint occurred in 0 out of 54 cases with the monoaxial VLP and in 4 out of 55 cases with the polyaxial VLP. Therefore, osteosynthesis using the polyaxial VLP was considered to be more prone to technical errors.…”
Section: Discussionmentioning
confidence: 99%